Geologic map of southeastern Seward Peninsula, Alaska / U.S. Geological Survey; Alfred H. Brooks geologist in charge, topography by D.C. Witherspoon [et al] - Geological Survey (U.S.) (Washington, D.C. : Geological Survey (U.S.), 1911)
Relief shown by contours. "U.S. Geological Survey bulletin 44[?] Upper right corner of map torn so bulletin number and part of legend are missing. "Surveyed in 1900-1903-1909." Color 1:250,000